Drug Induced Hypersensitivity Syndrome Secondary to Phenobarbitone - Inamdar, Syed Zia; Jakanur, Seema; Katragadda, Pradeepthi; Janagond, Ajit; Paramagond, Mallinath; Kulkarni, Raghavendra Vinayakarao; Naikwadi, Akram; Koth, Ananth; Patil, Arvind (Indian Journal of Pharmacy Practice)
Phenobarbitone- a barbiturate, non-selective central nervous system depressant drug, primarily used as a sedative hypnotic and anticonvulsant in sub hypnotic doses. It has long term anticonvulsant effect, used in the treatment of generalized tonic-clonic and cortical local seizures. It is also effective in acute convulsive episodes associated with status epileptic’s cholera, eclampsia, meningitis, tetanus and toxic reactions to strychnine or local anesthetics. The present case report describes the occurrence of anticonvulsant drug induced hypersensitivity drug reaction followed after to the use of phenobarbitone in a pediatric patient prescribed to treat his seizure disorder. The suspected drug was immediately stopped and the patient was managed symptomatically. The causality assessment of the adverse effect revealed a “probable” causal relationship for the suspected drug and reaction was categorized as “moderately severe” in nature.
Keywords: Anticonvulsant; Hypersensitivity; Adverse drug reaction; Phenobarbitone; Barbiturate; Pediatric.